Pottery Industry during the Neolithic Pottery Age Case study: Orontes Valley(Tell Al-Shir, Tell Al-Kerkh, Tell Al-Amuq) (Damascus University Journal of Historical Studies, 2024)
This research deals with pottery Industry during the pottery Neolithic Age in Orontes Valley. It follows the descriptive approach in an analytical manner, and is divided into three sections. The first section is devoted to defining the site of Tell Al-Shir and describing and studying the pottery discovered in it, while the second part covers the study of the Tell Al-Kerkh site, as well as the study of the pottery discovered in it, while the third part covers to the study of the Tell Al-Omuq site, and the study of the pottery discovered in it. The results of studies of the latest archaeological research and excavations in the aforementioned archaeological sites have been relied upon as a main source of information. The originality of this research comes from the fact that it is considered the first research dealing with the pottery industry in the Pottery Neolithic Age in the Orontes Valley, according to recent archaeological discoveries, in one integrated research that contributes to giving an integrated idea of that industry at the time. As for its borders, it includes geographically the Orontes Valley in Syria only. While chronologically, it includes the pottery Neolithic Age, dated to about 7100 / 7000 to 6200 BC. With regard to its objective limits, it is represented by describing the pottery discovered in each of the aforementioned sites separately, in terms of types, manufacturing and decoration techniques, types of decorations, how to use, etc., and then answer questions. presented in this research.
Keywords: Pottery; Pottery Neolithic Age; Syria; Shir; Kerkh; Amuq.